A eficácia do IPTU progressivo como instrumento de planejamento urbano : a experiência do município de Assis, SP - Floeter, Roberto de Almeida (Universidade Federal de São Carlos, 2007)
The research at issue broaches the application of progressive escalation in the County Real Property Tax (IPTU) of empty lots in Brazilian towns, the so-called Progressive IPTU collected in the county of Assis (SP) from 1977 to 2006. The urbanization and urban growth process which speeded up in Brazil from 1940 on and whose dynamics did not make any difference concerning geographical scales (large cities, average towns, small villages) reckoned upon the help of the main social, economical, and political agents involved in the production and sale process of the urban space, which left some distinguishing marks on Brazilian cities and towns such as the indiscriminate opening of new property developments, the boundless expansion of urban space, the precarious condition of low-cost dwellings, the banishment of the needy to the poor outskirts of cities and towns and the great amount of urban areas and lots left empty waiting for public investments and its following appreciation in value. One shows the considerable effort expended along the last forty years by organized sectors of society in favor of an urban reform and the introduction of various devices and means such as the Progressive IPTU into the Federal Constitution. The county of Assis (SP) is a remarkable case, for in 1977 it introduced a tax collection model to progressively levy county real property tax on empty lots, making it an effective means to achieve urban tax collection and planning. IPTU and its progressive quality became an important urban policy device in order to fight tax iniquities, to improve and to provide benefits and wealth to the population. Unfortunately, political changes effected in the county administration and political pressure put on by sectors linked to urban real property owners defaced that model and changed IPTU into a mere tax collection device, without pointing out its importance as a means to fight real property speculation and the implementation of the County Bylaws.
Keywords: Planejamento urbano; Imposto predial e territorial urbano (IPTU); Políticas públicas; ENGENHARIAS